P7 The safety of bronchoalveolar lavage in patients with idiopathic pulmonary fibrosis. (12th November 2019) - Smith, J; Chua, FJ; Wells, AU; Renzoni, E; Nicholson, AG; Jenkins, RG; Marshall, RP; Fahy, WA; Maher, TM; Molyneaux, PL
Abstract : Introduction: Retrospective and anecdotal evidence have been used to suggest that bronchoscopy in patients with IPF could be associated with an increased risk of acute exacerbations or acute respiratory deterioration. We aim to clarify the safety of BAL in patients with IPF in the prospectively recruited PROFILE cohort. Methods: Patients diagnosed with IPF within the past 6 months were invited to participate in the PROFILE study. Patients were assessed at baseline, 1, 3, and 6 months and annually for 3 years. Fibreoptic bronchoscopy with BAL was performed at baseline in a subset of the Royal Brompton portion of the cohort. The procedure involved installation of 240 ml of warm saline in four aliquots into the right middle lobe followed by gentle aspiration by hand.Continuous variables are presented as means (±SD) and categorical variables as proportions. Differences between subject groups were evaluated with the use of the Mann–Whitney test for continuous variables and Fisher exact test for categorical variables. Time-to-event curves were calculated using the Kaplan–Meier method and compared with the use of the log-rank test. Results: 302 patients were prospectively recruited, of whom 223 underwent bronchoscopy (74%). The 79 IPF patients who did not undergo BAL were older (71.6 vs. 67.8 years, P = 0.001) and had a lower DLCo (39.2% vs. 47.6%, P = 0.001) compared to subjects undergoing bronchoscopy. All subjects in the bronchoscopy cohort tolerated the procedure well. A leukocyte differential profile was determined in all cases and no immediate (<72 hrs) complications were reported. In the first 30 days post BAL, 6 patients (2.6%) reported complications including two with transient viral symptoms, one with odynophagia and three with a lower respiratory tract infection. Antibiotics were prescribed in all cases and one patient attended A&E. All-cause mortality at 90 days was 1.4% in the bronchoscopy cohort compared to 6.3% in the non-procedure cohort. The median survival for patients undergoing bronchoscopy was 3.7 years (figure 1). Conclusions: Bronchoscopy is a safe and well tolerated procedure in patients with IPF supporting its use as part of the diagnostic assessment of interstitial lung disease and as a research tool.